KOMUNIKASI INTERPERSONAL PENYANDANG TUNA WICARA (STUDI KASUS BAPAK TOING JURU PARKIR GEDUNG M. SYAFEI KOTA PADANG PANJANG) - Dela Sanita; Syafwan Rozi (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the interpersonal communication of Persons with Disabilities Speech by Mr. Toing as a parking attendant at the M. Syafei building, Padang Panjang City. The methodology in this study is a type of descriptive research with a approach qualitative and case study methods. The primary data sources are Irman or Mr. Toing, who works as a parking attendant at the M. Syafei building, Padang Panjang City and secondary data, namely family, working people, service users and secondary data from sources of books, journals, internet, thesis and others. While in data collection In this study the researchers collected data from observations, interviews and documentation. Based on the results of the study, it can be concluded, first, the supporting factors in interpersonal communication against the speech impaired is a factor that makes a communication can run smoothly and create a sense of security and comfort for the perpetrators communication, such as support, openness, trust and empathy. Second the inhibiting factor of interpersonal communication for people with speech impairments is a factor which causes communication problems such as technical problems, semantics (language) and physical disorders. Third, the communication model used is an interactive communication model where this model is very relevant because in doing Mr. Toing's daily work and interacting with users services or people who park in the building give each other a feedback effect so that vehicles can be parked in the right position, and to support their work use language or gestures so that people understand what is being said. Keywords: Interpersonal Communication, Speech Impaired